Surface Modification of Gold Nanoparticles to Improve Cancer Cell Targeting - Chen Mei; Wang Jing; Liu Yang (Journal of Biomedical and Techno Nanomaterials, 2024)
Gold nanoparticles (AuNPs) are promising agents for cancer therapy due to their unique properties, but effective targeting remains a challenge. Surface modification with specific ligands can enhance targeting efficiency. To develop and optimize surface-modified AuNPs to improve targeting of cancer cells, enhancing therapeutic outcomes while minimizing side effects. The study employed theoretical modeling, laboratory experiments, and in vivo testing. Cancer cell lines (MCF-7, A549, PC-3) and mouse models with human tumors were used to evaluate targeting efficiency. Instruments included TEM, SEM, DLS, zeta potential analysis, and HPLC. Surface-modified AuNPs showed an 80% increase in cancer cell binding compared to unmodified AuNPs. In vivo studies demonstrated a 70% reduction in tumor volume in treated mice. Stability tests indicated consistent performance under various biological conditions. Surface modification of AuNPs with specific ligands significantly enhances their targeting ability and therapeutic efficacy against cancer cells. Further clinical trials are necessary to validate these findings for clinical application.